108k views
4 votes
What is the answer??




What is the answer?? ​-example-1
User Tim Schoch
by
5.3k points

2 Answers

5 votes

Explanation:

X²+6x+6

now breaking 6x into 2x and 3x we get ,

X²+3x+2x+6

taking x common and 2 common we get ,

x(x+3)+2(x+3)

taking (x+3) common

(x+3) (x+2)

so comparing with zero to get values of x ,

either

x+3=0

x=-3

or x+2=0

x=-2

User Mabs
by
5.2k points
3 votes

Answer: x = -3 + √3 or x = -3 - √3

User Tarun Konda
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.